Subclinical gait disturbance and postoperative gait improvement in patients with degenerative cervical myelopathy - Dong-Ho Lee (Nature Portfolio, 2021)
Abstract This study aimed to evaluate the subclinical gait abnormalities and the postoperative gait improvements in patients with degenerative cervical myelopathy using three-dimensional gait analysis. We reviewed the gait analysis of 62 patients who underwent surgical treatment for degenerative cervical myelopathy. The asymptomatic gait group included 30 patients and the gait disturbance group included 32 patients who can walk on their own slowly or need assistive device on stairs. The step width (17.2 cm vs. 15.9 cm, P = 0.003), stride length (105.2 cm vs. 109.1 cm, P = 0.015), and double-limb support duration (13.4% vs. 11.7%, P = 0.027) improved only in the asymptomatic gait group. Preoperatively, the asymptomatic gait group exhibited better maximum knee flexion angle (60.5° vs. 54.8°, P = 0.001) and ankle plantarflexion angle at push-off (− 12.2° vs. − 6.5°, P = 0.001) compared to the gait disturbance group. Postoperatively, maximum knee flexion angle (62.3° vs. 58.2°, P = 0.004) and ankle plantarflexion angle at push-off (− 12.8° vs. − 8.3°, P = 0.002) were still better in the asymptomatic gait group, although both parameters improved in the gait disturbance group (P = 0.005, 0.039, respectively). Kinematic parameters could improve in patients with gait disturbance. However, temporospatial parameters improvement may be expected when the operative treatment is performed before apparent gait disturbance.